PERSPEKTIF PENDIDIKAN ISLAM TERHADAP FILSAFAT PERENIALISME - Zainal Abidin (Nizham Jurnal Studi Keislaman, 2014)
As a branch of philosophy ideologi perrenialism have follower especially in the modern philosophy. Perrenialism at the sight of all theory that every velues live at the past time can be influenced today’s and here, thus human being must be continued to conserve in the modern era. For this perspective perrenialism can be defined as continuing throught the whole years or lasting for very long time. And for the educational perspective perrenialism have a role to playing for important aspect in the development of educational construction because perrenialism trying to keep eternal values for next generation. To the Islamic thinker there some philosopher have perennial category, they introduced some perspective that different from other thinker like, ishrâqi, irfâny, and hikmah muta’âliyah can be influemced and introduced to construct for Islamic education study, especially to developed the new paradigm in Islamic educational thingking.